Representation and Presence: Divine Names in Judaism and Islam. (April 2021) - Ben-Sasson, Hillel
Abstract: Divine names are linguistic objects that underlie the grammar of religious language. They serve as both representations and presentations of the divine. As representations, divine names carry information pertaining to God's nature or actions, and his unique will, in a manner that adequately represents him. As presentations, divine names are believed to somehow effect divine presence in proximity to the believer, opening a path of direct connection to God. This paper seeks to analyze the interaction between presentation and representation concerning divine names in major trends within Judaism and Islam, from the Hebrew Bible and the Qur'an to medieval theological debates. It aims to demonstrate how central currents within both traditions shaped the intricate relation between divine presentation and representation through the prism of divine names. Whereas positions in philosophy of language focus on either the representational or the presentational functions of proper names, Jewish and Islamic theologies suggest ways to combine the two functions with regard to divine names.